Effects of different nutrient solutions on growth and flower quality of gerbera (Gerbera jamesonii) grown in hydroponic close system - Le, Thi Thuy; Nguyen, Thi Mai; Nguyen , Phuong Thao; Pham, Thi Van (Hue University Journal of Science: Natural Science, 2021)
The nutrient solution is the decisive factor for the growth and development of hydroponic plants. This study was conducted to determine the effect of five nutrient solutions, namely, Hoagland, Knop, Hydro Umat F, BKFAST, and Bio-Life, on the growth and development of gerbera (Gerbera jamesonii) in the hydroponic system. The results show that Hydro Umat F is the most suitable solution for planting gerbera in terms of plant height, number of leaves, leaf size, and root volume. In addition, the flower yield of the gerbera plants nourished on Hydro Umat F is also the highest, with 8.7 flowers per plant after five months in the hydroponic system. The flowers have a diameter of 9.8 cm and natural durability of 19.67 days. Meanwhile, gerbera plants stop growing after 15 days in the Bio-Life solution and 30 days in the Knop solution.